Republic of Armenia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The Poverty Reduction Strategy Paper (PRSP) has been developed for eradicating poverty in Armenia. It analyzes the poverty situation of Armenia, and evaluates the methodology and methodological issues. It discusses the PRSP goals, main policy directions, solution to poverty, and the reduction of inequality. It assesses the social and economic strategies and governance. It reviews the employment issues and trends in the budget framework, and also analyzes the implementation, monitoring, and evaluation of the system.